2022
DOI: 10.1126/sciadv.abk2855
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput and high-content bioassay enables tuning of polyester nanoparticles for cellular uptake, endosomal escape, and systemic in vivo delivery of mRNA

Abstract: Nanoparticle-based mRNA therapeutics hold great promise, but cellular internalization and endosomal escape remain key barriers for cytosolic delivery. We developed a dual nanoparticle uptake and endosomal disruption assay using high-throughput and high-content image-based screening. Using a genetically encoded Galectin 8 fluorescent fusion protein sensor, endosomal disruption could be detected via sensor clustering on damaged endosomal membranes. Simultaneously, nucleic acid endocytosis was quantified using fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 49 publications
1
89
0
Order By: Relevance
“…Due to the large molecular weight and negative charge of mRNA, it cannot passively cross the cell membrane. Additionally, it can be easily degraded by nuclease existing in the extracellular space. Lipid nanoparticles (LNP) are so far the most successful delivery platform that can facilitate cellular uptake of mRNA while preventing it from degradation. , Lung-specific delivery of mRNA has been achieved by high-throughput screening or rational design. For example, in 2016, Anderson et al achieved systemic delivery of mRNA to the lung first using hybrid polymer–lipid nanoparticles, which were composed of poly­(β-amino esters) (PBAEs) and lipid-polyethylene glycol (PEG) . Motivated by this potential outcome, they optimized polymer structures as well as nanoparticle formulations in 2018 and developed new PBAEs that were universal for the systemic delivery of mRNA and pDNA to the lung in 2021. , Furthermore, Xu et al identified lipidoids whose tails containing amide bonds were able to deliver mRNA to the lung .…”
mentioning
confidence: 99%
“…Due to the large molecular weight and negative charge of mRNA, it cannot passively cross the cell membrane. Additionally, it can be easily degraded by nuclease existing in the extracellular space. Lipid nanoparticles (LNP) are so far the most successful delivery platform that can facilitate cellular uptake of mRNA while preventing it from degradation. , Lung-specific delivery of mRNA has been achieved by high-throughput screening or rational design. For example, in 2016, Anderson et al achieved systemic delivery of mRNA to the lung first using hybrid polymer–lipid nanoparticles, which were composed of poly­(β-amino esters) (PBAEs) and lipid-polyethylene glycol (PEG) . Motivated by this potential outcome, they optimized polymer structures as well as nanoparticle formulations in 2018 and developed new PBAEs that were universal for the systemic delivery of mRNA and pDNA to the lung in 2021. , Furthermore, Xu et al identified lipidoids whose tails containing amide bonds were able to deliver mRNA to the lung .…”
mentioning
confidence: 99%
“…It is also possible that types of cells, other than immune cells, may be transfected. In the case of nanoparticles capable of delivering mRNA to the spleen, gene expression has been confirmed in cells other than immune cells, including endothelial cells [26]. However, transfection of these cells would not be expected to affect the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…PBAE nanoparticle binding, uptake and escape have been previously described in comparison to PEI, 7 , 15 , 29 and the development of a galectin 8-based biosensor enabled detection and comparison of endosomal escape of PBAEs versus various PEI constructs. 30 Bishop and Kozielski et al review various structural elements, such as charge density, hydrophobicity, and molecular weight, of PBAEs, PEI, and other biomaterials that help facilitate intracellular delivery of nucleic acids. 15 Karlsson et al review additional PBAE gene delivery mechanisms, giving a comprehensive description of studies investigating topics such as the binding strength of PBAEs, the effect of surface charge on toxicity, and the buffering capacity of PBAEs based on secondary and tertiary amines leading to endosomal escape.…”
Section: Discussionmentioning
confidence: 99%